Update on Indications for Red cell transfusion. (June 2016) - Ang, A. L.
Abstract : The first successful blood transfusion in human took place in the early 19th century. However, blood transfusion became an established clinical practice only in the 20th century as the need to treat large numbers of war casualties during the First and Second World Wars propelled the improvement in transfusion‐related knowledge and technology, resulting in safer and more effective blood collection and transfusion. The benefits of blood (or red cell) transfusion were first recognized and demonstrated in patients with massive haemorrhage and haemorrhagic shock. In such patients, securing haemostasis remains the most important therapeutic goal. Red cell transfusion also helps to quickly restore arterial oxygen content, and together with other measures such as fluid resuscitation, it helps to restore oxygen delivery to tissues. For patients with non‐haemorrhagic isovolaemic anaemia or non‐massive bleed who are haemodynamically stable, there may be differences in their tolerance of anaemia due to variations in their ability to recruit physiological reserves depending on their age and comorbidities. Therefore, decision to transfuse red cells in these patients should not be based purely on their haemoglobin (Hb), but should also depend on their clinical assessment. As the randomized controlled trial on Transfusion Requirements in Critical Care was first published in the late 1990s, more randomized controlled trials were conducted, showing non‐inferiority of a restrictive transfusion strategy compared to a liberal strategy in most clinical settings despite a significantly lower transfusion requirement. However, a safe Hb threshold for red cell transfusion in high‐risk patients such as those with acute coronary syndrome remains unknown, and larger randomized controlled trials are needed.